(untitled) (Economics and region, 2019)
The present article contains a study of the contemporary principles of enterprise management. As it is known, the principles are the basis of knowledge about the processes and phenomena. These named principles such as goal, planning, strategy, management, and control give the correct direction to achieve the maximum profitability of the product production. Modern marketing today is the most important field of activity of any enterprise which task is to bind the processes of the enterprise and the customers with a purpose of satisfying the customers’ needs and receiving the profit by the enterprise. Marketing functions can be very large, but they are subject to one of the most important goals such as profit and the existence of the enterprise in the long-term outlook. Marketing service at the company as a basis for their activities uses a complex market research to identify market conditions, demand’s dynamics and structure, market content evaluation, competitors and its own position at the market. Successfully organized and done work on the marketing helps to quickly detect and eliminate the shortcomings in the strategic planning, organization and implementation of commercial activities. Marketing management is an essential component part of the overall enterprise’s management system. It is impossible to imagine a successful enterprise that develops without application of marketing principles. Thus, the formation of the marketing activities of the enterprise should determine the principles by which marketing activities inherent to each individual enterprise will be formed. Proper use of marketing management principles will help the enterprise to survive in a tough competitive environment.